Evaluation of antibacterial activity on different solvent extracts of Euphorbia caracasana Boiss and Euphorbia cotinifolia L. (Euphorbiaceae) collected in Venezuela - Janne Rojas (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2008)
In the present investigation the evaluation of the antibacterial activity of Euphorbia caracasana Boiss and Euphorbia cotinifolia L. has beenevaluated against Gram positive and Gram negative bacteria using the disc diffusion agar method. E. caracasana and E. cotinifolia leaves were extracted with isopropyl alcohol. These extracts, after concentration, were fractionated by column chromatography and selected fractions, based on their TLC profiles, tested for antibacterial activity. Fractions eluted with dichloromethane/methanol 1:1 from the column chromatography of E. caracasana extract showed antibacterial activity against S. aureus ATCC 25923 at concentrations of 336 μg/mL and 33,6 μg/mL (dilution 1:10 of the same extract). Fractions eluted with n-hexane-dichloromethane 1:1 and dichloromethane from the samecolumn, lacked of antibacterial activity. None of the fractions eluted from the column separation of E. cotinifolia extract showed antibacterial activity in any of bacteria tested.